2023
DOI: 10.1097/rlu.0000000000004534
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT in a Case of Lung Adenocarcinoma With Diffuse Cavitary Intrapulmonary Metastases

Abstract: We describe FDG PET/CT findings in a case of lung adenocarcinoma with diffuse cavitary intrapulmonary metastases at initial diagnosis. High-resolution CT of the chest showed the primary solid tumor in the right upper lobe and numerous cavitating metastases ranging from a few millimeters to 1 cm in the bilateral lungs. FDG PET/CT showed intense activity of the primary tumor, diffuse activity of the lung metastases, and hypermetabolic metastases in the mediastinal lymph nodes and bones. Familiarity with this aty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The patient dies 9 months after the histological diagnosis. SMARCA4-deficient tumors are characterized by low differentiation and high malignancy throughout the body 1–3 . Biliary tract adenocarcinoma with SMARCA4 deficiency is rare and limited in the literature 4 .…”
mentioning
confidence: 99%
“…The patient dies 9 months after the histological diagnosis. SMARCA4-deficient tumors are characterized by low differentiation and high malignancy throughout the body 1–3 . Biliary tract adenocarcinoma with SMARCA4 deficiency is rare and limited in the literature 4 .…”
mentioning
confidence: 99%
“…Hu et al 9 reported a case with multiple hypermetabolic soft tissue lesions in the lung, whose diagnosis was confirmed as intestinal-type adenocarcinoma, whereas our case manifested as diffuse intense FDG uptake in both lungs. Widespread abnormal FDG activity in both lungs can be seen due to many different etiologies 10–15 . Pulmonary enteric adenocarcinoma should be included in the differential diagnoses in interpreting similar FDG PET/CT findings.…”
mentioning
confidence: 99%